Effects of Natura 2000 on nontarget bird and butterfly species based on citizen science data. Issue 3 (14th May 2020) - Pellissier, V.; Schmucki, R.; Pe'er, G.; Aunins, A.; Brereton, T. M.; Brotons, L.; Carnicer, J.; Chodkiewicz, T.; Chylarecki, P.; del Moral, J. C.; Escandell, V.; Evans, D.; et al.
Abstract: The European Union's Natura 2000 (N2000) is among the largest international networks of protected areas. One of its aims is to secure the status of a predetermined set of (targeted) bird and butterfly species. However, nontarget species may also benefit from N2000. We evaluated how the terrestrial component of this network affects the abundance of nontargeted, more common bird and butterfly species based on data from long‐term volunteer‐based monitoring programs in 9602 sites for birds and 2001 sites for butterflies. In almost half of the 155 bird species assessed, and particularly among woodland specialists, abundance increased (slope estimates ranged from 0.101 [SD 0.042] to 3.51 [SD 1.30]) as the proportion of landscape covered by N2000 sites increased. This positive relationship existed for 27 of the 104 butterfly species (estimates ranged from 0.382 [SD 0.163] to 4.28 [SD 0.768]), although most butterflies were generalists. For most species, when land‐cover covariates were accounted for these positive relationships were not evident, meaning land cover may be a determinant of positive effects of the N2000 network. The increase in abundance as N2000 coverage increased correlated with the specialization index for birds, but not for butterflies. Although the N2000 network supports high abundance of a large spectrum of species, the low number of specialist butterflies with a positive association with the N2000 network shows the need to improve the habitat quality of N2000 sites that could harbor open‐land butterfly specialists. For a better understanding of the processes involved, we advocate for standardized collection of data at N2000 sites. Abstract : Article impact statement : Across Europe the abundance of a majority of nontarget birds and a quarter of nontarget butterflies increased with Natura 2000 coverage. Abstract : Efectos de Natura 2000 sobre las Especies No Focales de Aves y Mariposas con Base en Datos de Ciencia Ciudadana Resumen: La red Natura 2000 (N2000) de la Unión Europea está entre las redes internacionales más grandes de áreas protegidas. Uno de sus objetivos es asegurar el estado de un conjunto predeterminado de especies de aves y mariposas (focales). Sin embargo, las especies no focales también pueden beneficiarse con la N2000. Evaluamos cómo el componente terrestre de esta red afecta la abundancia de las especies de aves y mariposas no focales más comunes con base en los datos de programas de monitoreo voluntario a largo plazo en 9, 602 sitios para aves y en 2, 001 sitios para mariposas. En casi la mitad de las 155 especies de aves evaluadas, particularmente entre aquellas especies especialistas en zonas boscosas, la abundancia incrementó (los estimaciones de la pendiente variaron desde 0.101 [DS 0.042] hasta 3.51 [DS 1.30]) conforme incrementó la proporción del paisaje cubierto por sitios de la N2000. Esta relación positiva existió en 27 de las 104 especies de mariposas (con una variación de estimaciones desde 0.382 [DS 0.163] hasta 4.28 [DS 0.768]), aunque la mayoría de las especies de mariposas fueron generalistas. Cuando se consideraron las covarianzas de cobertura de suelo estas relaciones positivas no fueron evidentes para la mayoría de las especies, lo que significa que la cobertura de suelo puede ser una determinante de los efectos positivos de la red N2000. El incremento en la abundancia conforme aumentó la cobertura de la N2000 estuvo correlacionado con el índice de especialización de las aves, pero no el de las mariposas. Aunque la red N2000 sostiene la abundancia alta de un espectro amplio de especies, el bajo número de mariposas especialistas con una asociación positiva a la red N2000 demuestra la necesidad de mejorar la calidad del hábitat de los sitios N2000 que podrían albergar a mariposas especialistas de campo abierto. Para un mejor entendimiento de los procesos involucrados, promovemos una recolección estandarizada de datos en los sitios de la red N2000. 摘要: 欧盟的 Natura 2000(N2000) 是全球最大的保护地网络之一, 它的目标之一是保护一批目标鸟类和蝴蝶物种的现状。不过, 非目标物种也可能从 N2000 中获益。本研究评估了该网络陆地保护区如何影响更为常见的非目标鸟类和蝴蝶的丰度, 所用数据来自长期的志愿者监测项目, 包括了 9602 个鸟类监测点和 2001 个蝴蝶监测点。在评估的 155 种鸟类中, 几乎一半的鸟类, 特别是林地专性种, 在 N2000 位点覆盖的景观比例上升时数量增加 (斜率估计值在 0.101 [SD 0.042] 到3.51 [SD 1.30] 之间) 。虽然大多数蝴蝶都是广幅种, 但 104 种蝴蝶中也有 27 种存在这种正相关关系 (斜率估计值在 0.382 [SD 0.163] 到 4.28 [SD 0.768]) 。对于大多数物种来说, 当考虑土地覆盖协变量时, 这样的正相关关系并不明显, 这意味着土地覆盖可能是 N2000 网络能否对物种产生积极影响的关键因素。物种的丰度随着 N2000 覆盖度增加而增加的现象与鸟类的生境特化指数相关, 而在蝴蝶中则无关。虽然 N2000 网络使许多物种得以维持较高丰度, 但获得其积极影响的蝴蝶专性种数量仍较少, 这说明需要在 N2000 网络中提高专性生活在开阔地的蝴蝶的生境质量。为了更好地理解其中的过程, 我们建议收集更多标准化的 N2000 位点数据。 【翻译: 胡怡思; 审校: 聂永刚】